PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA APOTEK YOSIN FARMA DI SITUBONDO - Maulida, Leny Hartia; Kusnadi, Edy; Wiryaningtyas, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is the most important part in selling and distributing goods from producers to consumers. The success of product marketing depends on what strategies are used to market their products to consumers. The purpose of this study was to analyze and examine the effect of service quality on consumer loyalty with consumer satisfaction as an intervening variable at Yosin Farma Pharmacy in Situbondo. This study uses a quantitative approach. The population in this study were the consumers of the Yosin Farma Pharmacy. The sampling technique was carried out using random sampling. Data analysis and hypothesis testing in this study used a structural equation model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that service quality has a significant effect on consumer satisfaction, service quality has not been proven to have a significant effect on consumer loyalty, consumer satisfaction has a significant effect on consumer loyalty. The results of the indirect effect hypothesis test show that the service quality variable on consumer loyalty through consumer satisfaction has a positive and significant effect.